2006
DOI: 10.1175/jam2322.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Large-Eddy Simulations of Flow in a Steep Alpine Valley. Part I: Methodology, Verification, and Sensitivity Experiments

Abstract: This paper investigates the steps necessary to achieve accurate simulations of flow over steep, mountainous terrain. Large-eddy simulations of flow in the Riviera Valley in the southern Swiss Alps are performed at horizontal resolutions as fine as 150 m using the Advanced Regional Prediction System. Comparisons are made with surface station and radiosonde measurements from the Mesoscale Alpine Programme (MAP)-Riviera project field campaign of 1999. Excellent agreement between simulations and observations is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
175
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(182 citation statements)
references
References 46 publications
7
175
0
Order By: Relevance
“…Overall the numerical modelling studies showed that simply increasing spatial resolution without incorporating Chow et al (2006). This figure is available in colour online at www.interscience.wiley.com/qj 945 improved surface data gives unsatisfactory results.…”
Section: Numerical Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall the numerical modelling studies showed that simply increasing spatial resolution without incorporating Chow et al (2006). This figure is available in colour online at www.interscience.wiley.com/qj 945 improved surface data gives unsatisfactory results.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…As the single most critical parameter in obtaining good correspondence between simulated and observed flow characteristics, the soil moisture distribution was identified (De Wekker et al, 2005;Chow et al, 2006). A successful approach to obtain enough spatial detail in the soil moisture distribution consists of using a detailed distributed hydrological model.…”
Section: Numerical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…characterising the real valley environment. In particular, Chow et al (2006) clearly demonstrated the need for high-resolution datasets with a proper nesting procedure, in order to achieve agreement between simulations (obtained through the Advanced Regional Prediction System; ARPS) and observations. Furthermore, Weigel et al (2006) confirmed the reduced growth of the well-mixed layer determined by both cold-air advection in the alongvalley direction and subsidence of warm air from aloft.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Weigel et al (2006) confirmed the reduced growth of the well-mixed layer determined by both cold-air advection in the alongvalley direction and subsidence of warm air from aloft. Routinely operated mesoscale models have also been tested for their reliability in reproducing the structure of the convective boundary layer in the context of a valley (Doran et al, 2002;De Wekker et al, 2005;Chow et al, 2006;Weigel et al, 2007b), allowing the identification of the processes which require far greater care when compared to measurements.…”
Section: Introductionmentioning
confidence: 99%